(3af bQGAI GdShb (B/s - (3ehQjd, LjeSs; (3GdYGeQj, NGdO s ((3GdbGgQI(B: s (3OGQ GdaGQhb ddfTQ hGdJhRjY(B, s, 2007)
(3jVe GdYhGed GdhGbYI NGQL fWGb SjWQI GdTQcI, bQGAI GdEbJUGO Gdbhej, CSYGQ GdaGFOI hSjGSI GdMcheI, GdShb GdYGdej hCSYGQ GdUQa hejRGf GdeOahYGJ, GdEMJHGS GdMQGQj hCSYGQ GdWGbI hGdSdY, GdScGf hGdEJLGgGJ GdELJeGYjI hCfeGW GdMjGI, GdbhI GdTQGFjI hGdCQHGM hGdShb, GdYhGed GdhGbYI aj fWGb SjWQI GdTQcI, GdJcGdja hGdCSYGQ, GdJfHD HGdCQHGM hHCSYGQ GdCSge hGdJfHD ef NdGd fehPL ddJGQjN GdeGdj ddTQcIs
Keywords: (3GdCShGb(B- (3HMhKs; (3GdEbJUGOs